2020
DOI: 10.3389/fphys.2020.607239
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Expression of the Alpha Nicotinic Acetylcholine Receptor 7 in the Human Normal, Diabetic, and Preeclamptic Placenta and Products of Conception

Abstract: Preeclampsia (PE) and gestational diabetes (GD) are complications in advanced pregnancy while miscarriage for early pregnancy. However, the etiological factors are not well understood. Smoking has been associated with these complications as well as the sudden intrauterine deaths, sudden infant death, miscarriages, and still births. However, the immunolocalization of alpha 7 nicotine acetylcholine receptor (α7-nAChR) is not studied.Materials and Methods: α7-nAChR subunit expression was evaluated in 10 paraffin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…It should be mentioned that nAChRs-mediated entrance of Ca2+ ions into cells could be considered as one of the main reasons for such gene expression changes, since it can activate the cAMP response element-binding protein (CREB) [26]. As well, GDM-induced hypoxia leads to the thickening of the lining of blood vessels in the placenta that can justify more expressions of the studied receptors in endothelial cells [27]. In another study, Machaalani et al in 2015 showed that nAChR subtypes increase in the pre-eclamptic placenta.…”
Section: Discussionmentioning
confidence: 99%
“…It should be mentioned that nAChRs-mediated entrance of Ca2+ ions into cells could be considered as one of the main reasons for such gene expression changes, since it can activate the cAMP response element-binding protein (CREB) [26]. As well, GDM-induced hypoxia leads to the thickening of the lining of blood vessels in the placenta that can justify more expressions of the studied receptors in endothelial cells [27]. In another study, Machaalani et al in 2015 showed that nAChR subtypes increase in the pre-eclamptic placenta.…”
Section: Discussionmentioning
confidence: 99%
“…RVG can specifically recognize receptors on the surface BBB-specific receptor (such as nAChR 29,30 or γ-aminobutyric acid receptor 27 ) to deliver carriers into the CNS in a non-invasive way. The detection results showed that nAChR exists not only in the neuron but also in microglia, 31 such as endothelial cells 32 and Schwann cell. 33 However, RVG only infects neurons, not glial cells.…”
Section: Delivery Mechanism Of Rvg Peptidesmentioning
confidence: 99%